A cerebellar mechanism for learning prior distributions of time intervals - Devika Narain (Nature Portfolio, 2018)
Human timing behavior is biased towards previously encountered intervals and is predicted by Bayesian models. Here, the authors develop a computational model based in properties of the cerebellum to show how we might encode time estimates based on prior experience.